CLASSROOM INTERACTION IN ENGLISH SUBJECT AT SMP NEGERI 1 BERASTAGI - Steven Karta Ginting; Sumarsih Sumarsih; Busmin Gurning (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2017)
This study was aimed to find out the teacher and students talk percentage, teacher characteristics and the roles of the teacher during classroom interaction classroom interaction at SMPN 1 Berastagi in 2016/2017 academic year. This study used descriptive design. The subjects of this study were 38 students Grade VIII and an English teacher. The data were analyzed by using Flander’s formulates and interaction observation tally sheet. The instrument of collecting data ware observation tally sheet and video recording. The analysis showed that teacher talk percentage was 71,90 %  and  28, 09% for students. It was found that teacher was dominant in talking than student. The teacher highest characteristics found were teacher control means dominated by commands or direction and content cross which were dominated by lecturing and questioning. For the roles of teacher, the two highest were teacher as controller and teacher as resource. From the result the writer concludes that the students were passive in the classroom interaction, on the other hand teacher hold almost the whole activities in the classroom.     Key words: Classroom interaction, Flanders interaction analysis category system